Can We Predict Which Adolescents Will Engage in Outpatient Substance Abuse Treatment? - Grant IG Christie; Lynda M Bavin; Sophie Wills (SAGE Publishing, 2018)
Understanding which adolescents remain in substance abuse treatment may facilitate the development of effective strategies for enhancing engagement and retention. Using clinical service data from a large naturalistic sample of adolescents, we examined whether client characteristics predict retention in outpatient alcohol and other drug (AOD) treatment. χ 2 tests and multinomial logistic regressions were conducted to examine relationships between sociodemographic and substance use variables and clinic attendance. Client characteristics of ethnicity, sex, age, living situation (whether living with or away from family), and substance use severity were associated with retention in community AOD treatment. Pacific Island youth, females, 13- to 15-year olds, clients living with family, and clients with more severe substance use were generally more likely to be "engaged" with the service (ie, attended 4+ sessions) than their European and Maori, male, 16- to 19-year-old, and living away from home counterparts. These findings may inform more targeted engagement strategies in the future.